Muscle Ultrasound as Imaging Domain of Frailty - Bencivenga, Leonardo; Picaro, Francesco; Ferrante, Lorenzo; Komici, Klara; Ruggiero, Federico; Sepe, Immacolata; Gambino, Giuseppina; Femminella, Grazia Daniela; Vitale, Dino Franco; Ferrara, Nicola; Rengo, Carlo; Rengo, Giuseppe (Frontiers in Medicine, 2022)
Introduction: Frailty is a geriatric syndrome, a clinical state of vulnerability for developing dependency and/or death. Due to its multidimensional nature, Comprehensive Geriatric Assessment (CGA) constitutes the best strategy to evaluate frailty in older patients. Accumulation of deficits model synthesizes the global assessment of geriatric domains in the Frailty Index (FI) score. Muscle Ultrasound (MUS) has been employed to evaluate muscle mass wasting as tool to assess sarcopenia in late life. The present study aims to evaluate the association between CGA-based FI and MUS measures in a population of hospitalized older adults. Methods: Patients aged ≥65 years underwent CGA for the evaluation of the domains of health and functional status, psycho-cognition, nutritional status, socio-environmental condition. Following standard procedure, a CGA-based FI was elaborated, taking into account 38 multidimensional items. Muscle thicknesses (MT) of rectus femoris plus vastus intermedius was measured through MUS axial cross-section. Multivariable regression analysis was employed to determine factors associated with FI. Results: The study population consisted of 136 older patients, 87 males (63.9%), with median age of 74 (70-81) years, FI of 0.3 (0.21-0.46) and MT of rectus femoris plus vastus intermedius 29.27 (23.08-35.7) mm. At multivariable regression analysis, FI resulted significantly and independently associated with age and MT. Conclusion: MT of rectus femoris plus vastus intermedius, measured through MUS, resulted to be significantly related to FI in a population of hospitalized older patients. In the CGA-based assessment of frailty, MUS may constitute an additional imaging domain.